Osteoinduction Ability Of Human Adiposed Derived Mesenchymal Stem Cell (HADMSC) with Chitosan Scaffold Combination Towards Blood Serum Phosphorus Levels - Nindya Rizqi Anjani (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
Reconstruction of extensive bone tissue damage is a treatment with complication. Because moving the autologous tissue such as bone graft can cause complications that causes problems in the repair of extensive tissue damage so, the principle of tissue engineering (stem cells, bioreactor / growth factor, and scaffold) is used as an alternative to reconstruct damage to the tissue because it has many advantages. The combination of hADMSC and chitosan scaffold, is expected to trigger osteoinduction that can be expressed by osteogenic markers such as phosphorus levels in blood serum. To prove osteoinduction in a combination of Human Adiposed Derived Mesenchymal Stem Cell (hADMSC) and chitosan scaffold using blood serum phosphorus levels. This study used 12 groups with 5 sample each. Groups 1 to 4 were the negative control group at day 1,3,7, and 14. While groups 5 to 8 were the positive control group at day 1,3,7, and 14. Groups 9 to 12 were treatment groups at day 1,3,7, and 14. In the negative control group bone was only removed, in positive control group, bone was removed and chitosan scaffold was added, and in treatment group, bone was removed then, hADMSC and chitosan scaffold combination was added . Blood collection will be carried out in each group for examination of phosphorus levels in the blood serum. There were differences in phosphorus levels in blood serum in each group even though statistically there were only significant differences on day 14. The combination of hADMSC and chitosan scaffold caused a significant change in blood serum phosphorus levels on day 14 which means it triggers osteoinduction.